The impact of simulated soccer match-play on hip and hamstring strength in academy soccer players - Salter, J.; Cresswell, R.; Forsdyke, D. (Science and Medicine in Football, 2022)
Introduction: Together, the burden of hamstring and hip and groin injuries in soccer is substantial and the risk of re-injury in these areas is high. Reduced muscle strength has been identified as an important modifiable intrinsic risk factor of injury. However, little is known regarding the within-match changes in hip and hamstring muscle strength in order to inform early detection and management strategies. Methods: Seventy-one male soccer players (age, 19.2± 0.9yrs; height, 175.9± 5.8 cm; weight, 73±8.2 kg) from an international academy completed a fixed soccer-specific activity profile (SAFT90). Isometric hip and eccentric hamstring strength were measured after a standardised 5-min warm-up and repeated at half time and full time. Repeated-measures ANOVA were used to determine changes in muscle strength with magnitude-based decisions used to express probabilistic uncertainty. Results: Findings indicate that i) there was likely to very likely substantial changes in isometric hip strength (-9.9-15.7%) and ii) no substantial changes in eccentric hamstring strength (-2.6-5.1%). Discussion: By extrapolating these findings, it can be inferred that reduced isometric hip strength during match play may be one risk factor for injury, especially during periods of fixture congestion and practitioners should routinely assess muscle strength to inform training and match exposure based on player readiness. In doing so, it is likely that practitioners may enhance player availability and minimise injury incidence.